Extracellular Vesicles Secreted by Hypoxic AC10 Cardiomyocytes Modulate Fibroblast Cell Motility - Ontoria-Oviedo, Imelda; Dorronsoro, Akaitz; Sánchez, Rafael; Ciria, Maria; Gómez-Ferrer, Marta; Buigues, Marc; Grueso, Elena; Tejedor, Sandra; García-García, Francisco; González-King, Hernán; Garcia, Nahuel A.; Peiró-Molina, Esteban; et al. (Frontiers in Cardiovascular Medicine, 2018)
Extracellular vesicles (EVs) are small membrane vesicles secreted by most cell types with important roles in cell-to-cell communication. To assess their relevance in the context of heart ischemia, EVs isolated from the AC-10 ventricular cardiomyocyte cell line (CM-EVs), exposed to normoxia (Nx) or hypoxia (Hx), were incubated with fibroblasts and endothelial cells (EC). CM-EVs were studied using electron microscopy, nano particle tracking analysis (NTA), western blotting and proteomic analysis. Results showed that EVs had a strong preference to be internalized by EC over fibroblasts, suggesting an active exosome-based communication mechanism between CM and EC in the heart. In Matrigel tube-formation assays, Hx CM-EVs were inferior to Nx CM-EVs in angiogenesis. By contrast, in a wound-healing assay, wound closure was faster in fibroblasts treated with Hx CM-EVs than with Nx CM-EVs, supporting a pro-fibrotic effect of Hx CM-EVs. Overall, these observations were consistent with the different protein cargoes detected by proteomic analysis under Nx and Hx conditions and the biological pathways identified. The paracrine crosstalk between CM-EVs, Fb and EC in different physiological conditions could account for the contribution of CM-EVs to cardiac remodeling after an ischemic insult.